2005
DOI: 10.3168/jds.s0022-0302(05)72784-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Different Shapes of Lactation Curve for Milk Yield in Dairy Cattle by Empirical Mathematical Models

Abstract: The study of relationships between mathematical properties of functions used to model lactation curves is usually limited to the evaluation of the goodness of fit. Problems related to the existence of different lactation curve shapes are usually neglected or solved drastically by considering shapes markedly different from the standard as biologically atypical. A deeper investigation could yield useful indications for developing technical tools aimed at modifying the lactation curve in a desirable fashion. Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
188
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(223 citation statements)
references
References 28 publications
28
188
1
6
Order By: Relevance
“…Results obtained in this study for individual lactations of standard length agree with previous reports for dairy cattle (Olori et al, 1999;Macciotta et al, 2005;Silvestre et al, 2006), with a better fit for polynomials (AS, LEG and SPL) compared with models with three parameters. No studies are currently available in the literature on fitting individual extended lactation curves.…”
Section: Resultssupporting
confidence: 90%
“…Results obtained in this study for individual lactations of standard length agree with previous reports for dairy cattle (Olori et al, 1999;Macciotta et al, 2005;Silvestre et al, 2006), with a better fit for polynomials (AS, LEG and SPL) compared with models with three parameters. No studies are currently available in the literature on fitting individual extended lactation curves.…”
Section: Resultssupporting
confidence: 90%
“…When the first TD yield was at the end of the first month of lactation, the yields in the first month were extrapolated, and that might be why LEG3 and LEG4 very often modeled lactation curves without a peak, that is, as continuously decreasing curves. Macciotta et al (2005) confirmed that such atypical lactation curves were mainly a result of lack of records in the first days after calving. They also noticed that the occurrence of the curves without a peak arose from the peculiar combination of TD yields and their distribution along the entire lactation.…”
Section: Discussionsupporting
confidence: 52%
“…It should be added that Olori et al (1999) and Quinn et al (2005) considered weekly yields; what is more, Olori et al (1999) used only data on heifers from one herd, kept under uniform feeding and management conditions. Macciotta et al (2005) suggested that three-parameter models such as the WIL function ensured a superior fit to data with a single curvature. According to them, five-parameter functions like ALI and LEG4 are more flexible and permit description of a larger number of lactation curve shapes; that is why they were often used in random regression analyses of TD data to model individual deviations from an average fixed curve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations